3D Super-Resolution Optical Profiling Using Microsphere Enhanced Mirau Interferometry - Ivan Kassamakov; Sylvain Lecler; Anton Nolvi; Audrey Leong-Hoï; Paul Montgomery; Edward Hæggström (Scientific Reports, 2017)
Abstract We present quantitative three dimensional images of grooves on a writable Blu-ray Disc based on a single objective Mirau type interferometric microscope, enhanced with a microsphere which is considered as a photonic nanojet source. Along the optical axis the resolution of this microsphere assisted interferometry system is a few nanometers while the lateral resolution is around 112 nm. To understand the physical phenomena involved in this kind of imaging we have modelled the interaction between the photonic jet and the complex disc surface. Agreement between simulation and experimental results is demonstrated. We underline that although the ability of the microsphere to generate a photonic nanojet does not alone explain the resolution of the interferometer, the nanojet can be used to try to understand the imaging process. To partly explain the lateral super-resolution, the potential role of coherence is illustrated. The presented modality may have a large impact on many fields from bio-medicine to nanotechnology.